Colombia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2001)
This Selected Issues paper provides background information and analysis on recent developments and critical issues for the Colombian economy. The study discusses the unemployment and stresses in the financial system and also focuses on fiscal issues. The following statistical data are presented in detail: national accounts at current prices and at constant prices, savings and investment, value of agricultural crops, mining production, structure of regular gasoline prices, indicators of construction activity, minimum wages, producer price index, interest rates, and so on.